A behavioral intentions typology of attendees to an EDM festival in South Africa. Issue 4 (20th October 2018) - Kruger, Martinette; Viljoen, Armand; Saayman, Melville
Abstract: This study determined the characteristics and post-festival behavioral intentions of visitors attending one of the largest electronic dance music (EDM) festivals in South Africa to identify and profile the market segments who attend these types of festivals. Based on a visitor survey, music festival attendance, music appreciation, music tourism and sharing, and music purchasing were identified as the behavioral intentions likely to occur after attending the festival; from these, three distinct segments were identified: Erratic, Dynamic, and Motivated . This research, therefore, created an EDM typology of festival visitors, based on their behavioral intentions.